Employee Performance: The Effects of Supervision, Work Discipline, and Work Environment: Kinerja Karyawan: Pengaruh Supervisi, Disiplin Kerja, dan Lingkungan Kerja - Ridha Arizka Darmawan; Sumartik (Academia Open, 2024)
This study aims to describe and analyze the influence of supervision, work discipline, and the work environment on employee performance. A quantitative approach with hypothesis testing was employed, utilizing multiple linear regression analysis in SPSS version 22. The research sample consisted of 55 employees from an undisclosed organization. Primary data were collected through direct distribution of questionnaires measured using a Likert scale, validated, and tested for reliability. The findings reveal that supervision, work discipline, and the work environment have partial positive effects on employee performance, and collectively, they significantly enhance employee performance. This study contributes valuable insights into the multifaceted factors affecting employee performance, offering practical implications for organizations seeking to optimize their workforce productivity. Highlight: Comprehensive Analysis: This study employs quantitative methods to comprehensively analyze the impact of supervision, work discipline, and the work environment on employee performance. Partial Influences: The research highlights the individual partial influences of supervision, work discipline, and the work environment on employee performance, shedding light on their specific roles within the organizational context. Collective Enhancement: The study underscores the collective positive influence of these variables, emphasizing their combined impact on significantly improving overall employee performance. Keywords: Supervision, Work Discipline, Work Environment, Employee Performance, Quantitative Analysis